Transformation concept "Information technologies" in modern scientific discourse - Rubanets, O. (KNUCA, 2019)
The purpose of the study is to reveal the objective transformations that have occurred in information technology. Conceptualization of these transformations is also important. System, information, network and cognitive approaches allow to reveal the main aspects of the development of information technologies - technical and technological, software and hardware, network, communication, cognitive. The article considers the evolution of information technology. The relationship of information technology with its increasing role and importance of information in the life of man and society is analyzed. Information technologies are disclosed as technologies to create, store, record and process information. Technical and technological direction of information technology development is analyzed. The connection of the information technology concept transformation and development of the information society theory, in particular, the theory of post-industrial society, information society, network society, knowledge society and the digital world is revealed. The connection of the information technology concept transformation and the emergence of the media civilization and global information space is also revealed. The article shows that the development of information technology is an important factor in the development of the information society. Technology transition (the electronic computer as a machine) to the modern stage of development of digital technologies is characterized by the formation of a single technical and technological basis for the formation of the information society. The classification of information technology according to its application scope is proposed. Information and communication technologies characterize subject-to-subject interactions, among which pedagogical and political technologies are primarily distinguished. Information space is separate area of information technology application. Information processing technologies in the information space are the basis of modern democratic discourse. An important area of information technology is the information sphere. Information sphere is the sphere of information activity, information exchange and information relations, the regulator of which is the information law. Information security technologies ensure the protection of human rights, society and the state in obtaining objective information. Cybersecurity technologies protect critical infrastructure. The technologies of reality – virtual, cognitive, and augmented – provide the ability of a person’s consciousness and thinking to process and create new information. Identifying the social significance of the technical and technological development of information technologies becomes the basis of recommendations for the implementation of a strategies for the formation of the information society in Ukraine.
Трансформация концепта "информационные технологии" в современном научном дискурсе
Keywords: information technologies; information and communication technologies; network technologies; digital technologies